(untitled) (Research, Society and Development, 2020)
This study aims to unveil the teachers’ conceptions about the use of information and communication technologies in the educational context, specifically in the Basic Education of the city of Jaguaruana-Ceará, as well as its reflections on the developments of the insertion of these resources in the period of the COVID-19 pandemic, from remote education. Based on methodological procedures that mix quali-quantitative methods, having as reference the bibliographic research, from Santos (2009), Moran (2000), and the field research, because we used electronic questionnaires applied to teachers. Our findings allowed us to reflect that the adaptive process of teachers to remote education sometimes denotes the lack of familiarity with TDIC, sometimes demonstrates the attempt to learning from resources. Regarding the pedagogical practice in the schools of the municipality, the challenges denote: the limitations of initial and continued teacher training; the precariousness of the profession; the lack of physical infrastructure and technological resources in the institutions; the inaccessibility to the technological means by students and teachers, both at school at home and the absence of public policies for digital inclusion of school subjects. All these challenges marked by the deresponsibility of the State in the democratization of access and permanence in school/ scrapping of education. Therefore, we believe that before thinking about remote teaching, hybrid teaching should be the democratization of education and TDIC, because education is a constitutional right.